2019
DOI: 10.28991/scimedj-2019-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Bioactivity of Porous Bioglass Tablets for Bone Tissue Regeneration

Abstract: The present study endeavors in the preparation and characterization of semi crystalline 45S5 bioglass (BG) (SiO2-CaO-P2O5) through sol gel process. Dry press mold technique was used in the preparation porous BG tablets to examine the bioactivity through invitro studies. The synthesized BG powder was subjected to structural, morphological and mechanical characterization and the bioactivity was examined in vitro by immersing the BG tablet in the Simulated Body Fluid (SBF) solution. XRD pattern and the SEM microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…A 2013 systematic review reported that 4 RCTs found surgical intervention to be more successful than noninvasive treatment for managing pain and functional disability, while 1 RCT found no difference in future low back pain outcomes. [ 34 , 35 , 36 ] while our review also showed improvement in pain and functional disability.…”
Section: Discussionsupporting
confidence: 61%
“…A 2013 systematic review reported that 4 RCTs found surgical intervention to be more successful than noninvasive treatment for managing pain and functional disability, while 1 RCT found no difference in future low back pain outcomes. [ 34 , 35 , 36 ] while our review also showed improvement in pain and functional disability.…”
Section: Discussionsupporting
confidence: 61%
“…PMMA leakage is a focus point to surgeons because neurological or spinal cord damage may cause by the situation [12,18,30]. Traditionally, PMMA is injected into the preset nail tunnel using a PVP device during laddering period, and then the screw is inserted [25].…”
Section: Discussionmentioning
confidence: 99%
“…These patients may have had many comorbidities and severe osteoporosis, which resulted in complex surgical procedures might not be tolerated. In one study of Huang et al [30], they observed the clinical outcomes of traditional PMMA augmentation technology in 28 cases of Kummell's disease. The operation time, blood loss and hospitalization time were 115.9 ± 10.0 minutes, 214.3 ± 17.5 ml and 7.6 ± 1.3 days respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among various current strategies that augment the biomechanical stability of internal xation, polymethylmethacrylate-augmented cannulated pedicle screw (CPS) is currently considered the best strategy due to its high strength and rapid solidi cation [3,4]. Although this strategy is widely accepted by researchers, complications are common to be observed which mainly including nerve compression symptoms, pulmonary embolism and nerve injury due to intraoperative cement leakage (CL) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%